Pengendalian risiko pada lembaga publik: analisis terhadap sistem pengendalian manajemen Berbasis risiko - Rischa Herlina Nadapdap; Sayyida Nabila; Bebi Delpriman Gulo; Fiqri Haikal; Fitri Yani Panggabean (Tamilis Synex: Multidimensional Collaboration, 2025)
This study focuses on analyzing the effectiveness of risk-based management control systems in public institutions, designed to address internal and external dynamics affecting operations. The aim of this research is to evaluate how these systems assist in identifying and mitigating strategic, operational, financial, and compliance risks. The method employed involves a descriptive analysis approach by observing the implementation of these systems in several public institutions. The findings reveal that implementing such systems supports increased work efficiency, accountability, and public trust. Key success factors include leadership commitment, the development of human resource competencies, and the optimization of information technology. However, several challenges hinder implementation, such as limited resources, inadequate information technology, and regulatory complexities. This study concludes that continuous evaluation and improvement are crucial to strengthening risk control systems, making them more adaptive to support organizational goals and enhance public trust.